Réponses

2013-11-27T23:54:13+01:00
Bonsoir,

Tu veux dire : "passer d'une forme développée à une forme canonique" ?

2x^2+2x+12=2(x^2+x+6)

Or x² + x est le début d'une identité remarquable.

(x+\dfrac{1}{2})^2=x^2+x+\dfrac{1}{4}\ \ \Longrightarrow\ \ \ x^2+x=(x+\dfrac{1}{2})^2-\dfrac{1}{4}

Donc,  2x^2+2x+12=2(x^2+x+6)

2x^2+2x+12=2[(x+\dfrac{1}{2})^2-\dfrac{1}{4}+6]\\\\2x^2+2x+12=2[(x+\dfrac{1}{2})^2-\dfrac{1}{4}+\dfrac{24}{4}]\\\\2x^2+2x+12=2[(x+\dfrac{1}{2})^2+\dfrac{23}{4}]\\\\2x^2+2x+12=2(x+\dfrac{1}{2})^2+\dfrac{23}{2}